Knowledge and Self-Efficacy of Adolescents in the Prevention of Premarital Sexual Activity - Allania Hanung Putri Sekar Ningrum; Luluk Khusul Dwihestie; Triani Yuliastanti; Rismawati Rismawati (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Unhealthy sexual behavior among adolescents, especially unmarried adolescents, tends to increase. Risky sexual behavior has an impact on the high number of unwanted pregnancies and early marriages as well as the increasing number of HIV/AIDS cases among adolescents. According to Green, a person's behavior is influenced by; predisposing, supporting, and driving factors. From the preliminary study conducted in December 2023, students of Bhinneka Karya 2 Boyolali High School have low knowledge about premarital sexual behavior. The purpose of this study was to determine the relationship between knowledge, and self-efficacy with premarital sexual behavior in adolescents. The population in this study were students of class X SMA Bhinneka Karya 2 Boyolali as many as 50 teenagers. The sampling technique in this study was accidental sampling, which obtained a sample of 40 respondents. The data used in this study are primary data with a research instrument in the form of a questionnaire about knowledge, self-efficacy, and premarital sexual behavior in adolescents. Univariate analysis was performed by conducting frequency distribution analysis, while the bivariate analysis used was chi-square.